A COMPARATIVE STUDY OF INFRACLAVICULAR AND RETROCLAVICULAR BRACHIAL PLEXUS BLOCK FOR BELOW ELBOW SURGERIES (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Ultrasound-guided brachial plexus block is an effective regional anaesthetic technique for below elbow surgeries, providing excellent surgical anaesthesia and prolonged postoperative analgesia. The infraclavicular approach is widely practiced, whereas the retroclavicular approach has gained popularity because of improved needle visualization during ultrasound-guided block placement. This study compared the efficacy and safety of these two approaches. Methods: A prospective randomized comparative study was conducted in 80 adult patients (ASA physical status I–II) undergoing elective below elbow surgeries. Patients were randomly allocated into two equal groups. Group I received an ultrasound-guided infraclavicular brachial plexus block, whereas Group R received an ultrasound-guided retroclavicular brachial plexus block. Both groups received 30 mL of 0.5% ropivacaine with fentanyl 50 µg. The primary outcomes were onset and duration of sensory and motor block. Secondary outcomes included duration of postoperative analgesia, block performance time, haemodynamic changes, and procedure-related complications. Results: Both techniques achieved successful surgical anaesthesia with a high success rate. The retroclavicular approach demonstrated significantly better needle visualization and shorter block performance time (p